Electrochemical and Surface Analysis Studies on the Carbon Dioxide Corrosion of X-65 Carbon Steel - Alam, M.; Chan, E.; De Marco, Roland; Huang, Y.; Bailey, S. (Wiley - VCH Verlag GmbH & Co. KGaA, 2016)
© 2016 Wiley-VCH Verlag GmbH & Co. KGaA, WeinheimA comprehensive study of the CO2 corrosion of carbon steel (X-65) at low partial pressures of CO2 is reported in this paper. Field emission scanning electron microscopy (FESEM), Raman spectroscopy (RS), synchrotron radiation-grazing incidence X-ray diffraction (SR-GIXRD), and electrode kinetic studies have confirmed that chukanovite, magnetite and siderite are the main corrosion products at low partial pressures of CO2. Chukanovite forms predominantly in the presence of CO2, while magnetite was found to be the major corrosion product in the absence of CO2, although the majority of previous work based on conventional ex-situ materials characterization techniques has implied that siderite is the main corrosion product. Here, it is shown that the nature of corrosion products is strongly dependent on the experimental conditions at low pressures of CO2, which has not been elucidated in previous studies. Accordingly, this study has made a significant contribution to identifying the true nature of corrosion scales formed at low partial pressures of CO2 allowing the development of effective anti-corrosive agents for the control and prevention of carbon steel corrosion at low CO2 partial pressures.